PEMANFAATAN SILASE KERING AMPAS TAHU UNTUK PAKAN IKAN NILA MERAH (Oreochromis niloticus) - Arif Tribina (Jurnal Teknologi Perikanan dan Kelautan, 2012)
The advantage of diet is the most efficient of the number of diet towards fish growth and Feeding Conversion Ratio (FCR) in aquaculture. This research was done in order to discover the effect of different diet dosage towards fish growth and the water and 20 peaces of small fish (4,13 Â± 0,08 gr/peaces). This research used experimantal method in Radomized Complete Design (RCD). Tdiet dosage was: A = 3%; B = 5%; C = 7%; D = 9% Biomass weight/day and the replicated 3 times. Results show that the different diet dosage gave significant effect (P < 0,01) on fish specific growth rates and feeding conversion ratio. The best groeth rate and feeding conversion ratio was 4,47% biomass weight/day (4,47 gr/1 kg fish/day).